A study on factor influencing purchase intention of smartphone among university students in Melaka / Muhammad Zul Fathi Mohd Zulkifli - Mohd Zulkifli, Muhammad Zul Fathi (Faculty of Business and Management, 2020)
Smartphone is one of technology device that common use for many peoples in their daily life. This technology is very useful for their users to do several of activities in anytime and everywhere. Therefore, smartphone is one of platform that has side effect of good and bad for people which is it can show on how people use the smartphone. Some of good side is the user use the smartphone to have a communication with others, education and online learning while for bad side, the user use to do some illegal activities like fraud, scam, hacked and others. The purpose of this thesis is to know which factors is more influencing purchase intention of smartphone among university students. The most factors influence purchase intention of smartphone will help student to make a choice based on their preference. Other than that, the demand of smartphone will increase if the most influential will contribute to their chosen. The method used in this study is regression analysis which is it will explain on what factors will show significant or not significant. The techniques used to collect the data is by distribute a questionnaire to the target population that will more explain in Chapter 3. In this report, it will show the output of result to identify the most factors influencing purchase intention of smartphone among university students.